2003
DOI: 10.1002/pon.760
|View full text |Cite
|
Sign up to set email alerts
|

Relation of family history of prostate cancer to perceived vulnerability and screening behavior

Abstract: Men with a positive family history of prostate cancer are known to be at increased risk for the disease; however, relatively little is known about their risk perceptions or screening behavior. To address these issues, the current study examined the relationship of family history of prostate cancer to perceived vulnerability of developing prostate cancer and prostate cancer screening practices. Participants were 83 men with a positive family history of prostate cancer and 83 men with a negative family history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 16 publications
5
61
1
1
Order By: Relevance
“…In contrast to others (16), perceived risk does not mediate the relationship between family history and screening. It is possible that physicians were more likely to refer men with a family history of prostate cancer for PSA testing, whereas men with higher perceived risk initiated screening themselves.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast to others (16), perceived risk does not mediate the relationship between family history and screening. It is possible that physicians were more likely to refer men with a family history of prostate cancer for PSA testing, whereas men with higher perceived risk initiated screening themselves.…”
Section: Discussioncontrasting
confidence: 61%
“…However, in another study, men with a family history of prostate cancer (half of the sample of 166 men) reported greater perceived vulnerability and were more likely to report their intention to be screened and to have been screened in the past. Perceived vulnerability mediated the relationship between family history and intention to be screened (16). In summary, recent studies indicate that heightened perception of cancer risk and moderate worries are strong predictors of screening (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that men with a family history are more likely to have a PSA test (McDavid et al, 2000;Jacobsen et al, 2004), others found no association between family history and screening uptake (Taylor et al, 1999;Miller et al, 2001).…”
mentioning
confidence: 99%
“…14,15 As the contribution of BRCA2 and other genes to hereditary prostate cancer is clarified, 16,17 and the effectiveness of screening in men at increased risk becomes better understood, this situation may change. Meanwhile, it is likely that men with a family history of prostate cancer have unmet needs as they live with increased worry, 18 feelings of vulnerability about developing this condition, 19,20 and concern for their sons. 21 As a first step to developing genetic services for hereditary prostate cancer, this study aimed to identify the information and support needs of men with a family history of prostate cancer and to explore their preferences for how these needs could be met.…”
mentioning
confidence: 99%